Structure, development, and the salt response of salt bladders in Chenopodium album L. - Zhang, Yigong; Mutailifu, Ayibaiheremu; Lan, Haiyan (Frontiers in Plant Science, 2022)
Salt bladders are specialized epidermal structures that halophytes use to store and excrete excess salt. However, the cell wall composition during salt bladder development is unclear, and the functions of salt bladders in a few wild plants remain unexplored. Therefore, the present study examined salt bladder development, cell wall composition, and their roles under salt stress by employing bladder-brushed and unbrushed Chenopodium album plants. We found that the bladder cell of C. album was connected to the epidermal cells through a rectangular stalk cell and developed from the shoot tip and the young leaves. The polysaccharides of salt bladder cell wall showed dynamic distribution at different stages of development. Moreover, salt bladders affected Na+ and K+ accumulation, increased reactive oxygen species scavenging, and improved the osmoregulation and photosynthetic efficiency in leaves, subsequently enhancing the salt tolerance of plants. The ﬁndings strengthen our knowledge of the physiological mechanisms of the accessory structures in desert plants, which can be used as a reference for further research at the molecular level.